«ШӘРИЯР» ДӘСТАНЫНДА ҚАҲАРМАНЛАР ОБРАЗЛАРЫНЫҢ ЖАСАЛЫЎ ӨЗГЕШЕЛИКЛЕРИ - Кенесбаева, Ш.К. (SCIENCE and SOCIETY, 2020)
The article deals with the peculiarities of creating heroic images in the epos. Despite the fact that these characters passess all qualities of folklore works, being mythological-fantastic and fairy, they are realistic characters. The author cames to the conclusion, that the epos «Sharyar» is a mythological-fairy work in form and creation of heroic images, but such global issues as «good-evil», «justice-injustice» are narrated truthfully and on the high artistic level.
Keywords: epos; heroes of an epos; creation of the heroic image; realistic and folklore qualities; idea and image; image status